Editorial Note and Book Review: Natural Hazards and the Mitigation of their Impact - Sipos, György (Geographica Pannonica, 2022)
Under a changing climate and an intensifying human impact on the environment, managing and mitigat- ing natural hazards are increasingly important for our society to tackle the serious challenges of the future concerning population and economic growth, food safety, preservation of ecosystem services and biodi- versity; moreover, this task should be accomplished in a sustainable and eco-friendly way. Therefore, it is not enough to realise natural hazards and study their geographical aspects, but we need to learn and share the multitude of practices applied worldwide among specific conditions.